Use of the chop hook to stabilize the capsular bag in patients with crystalline lens dislocations and cataracts - Zeng, Yanfeng (J Int Med Res, 2017)
OBJECTIVE: To observe the treatment effects of chop hook-assisted phacoemulsification surgery in patients with crystalline lens dislocation. METHODS: Thirty-seven eyes with cataracts and crystalline lens dislocations underwent cataract surgery. An L-shaped chop hook was introduced into the anterior chamber, and the tip was pushed or pulled to the centre of the anterior capsular edge of the zonular dialysis during the cataract operation. Postoperative follow-up was conducted for ≥ 1 month. RESULTS: All patients’ postoperative visual abilities improved except one patient with glaucoma. One patient who underwent −5D intraocular lens implantation exhibited vision of 1/50. Visual acuity was less than 6/20 in 6 eyes, 6/20 to 10/20 in 7 eyes, and greater than 10/20 in 22 eyes. CONCLUSIONS: L-shaped chop hooks can be used to push or pull the anterior capsular edge of the zonular dialysis for protection and avoidance of further zonular damage. This strategy provides satisfactory effects and reduces use of additional instruments.